Overexpression of SLC40A1 inhibits the malignancy of hepatocellular carcinoma MHCC-97H cells by stimulation of autophagy. (May 2022) - Peng, Yu; Yang, Junqin; Li, Zedong; Chen, Sheng; Tang, Xianming; Zhou, Jun
Highlights: The overexpression of SLC40A1 will activate the autophagy flux and up-regulate autophagy by promoting the formation of autophagosomes. Overexpression of SLC40A1 can inhibit the proliferation, migration and invasion of liver cancer cells MHCC-97H. SLC40A1 up-regulates autophagy through AMPK/mTOR/ULK1 and AMPK/ULK1 signaling pathways. The expression of SLC40A1 will affect the iron content in the cell, and iron will affect energy production through the oxidized respiratory chain. AMPK is also an energy-sensing factor in cells. Increased AMP:ATP ratio activates AMPK. The activated AMPK up-regulates the level of autophagy through AMPK/mTOR/ULK1 and AMPK/ULK1 signaling pathways to meet the cell's energy requirements. While SLC40A1 overexpression positively regulates autophagy, it also reduces the proliferation, metastasis and invasion of liver cancer cells MHCC-97H. This tendency is significantly weakened after autophagy is inhibited. The expression level of SLC40A1 affects the intracellular iron content and thus the AMPK activity. Abstract: Our previous findings demonstrated that SLC40A1 expression in hepatocellular carcinoma (HCC) tissue was significantly lower than para -tumor tissues and normal liver tissue. SLC40A1 expression was associated with tumor staging, intrahepatic metastasis and portal vein invasion. However, the mechanism of SLC40A1 as a modulator of autophagy involving the invasion and metastasis of HCC was not clear. In the present study, we found that SLC40A1 overexpressed in MHCC-97H could activate the autophagic flux and further inhibit cells' capacity of proliferation, migration, and invasion. Correspondingly, the autophagy inhibitor chloroquine could restrain the autophagic level of MHCC-97H-SLC40A1 cells and increase their invasive capacity. Moreover, SLC40A1 modulated the autophagic level of MHCC-97H via the AMPK/mTOR/ULK1 and AMPK/ULK1 signaling pathways. Our findings showed that elevated expression of SLC40A1 suppressed the invasion and metastasis of HCC via activating autophagy. Therapeutics that interfere with the expression of SLC40A1 in HCC cells and promotion of autophagy may attenuate tumor progression and metastasis.